2013
DOI: 10.1002/j.1532-2149.2013.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

H‐coil repetitive transcranial magnetic stimulation for pain relief in patients with diabetic neuropathy

Abstract: Deep H-coil rTMS provides pain relief in patients with diabetic neuropathy. This innovative technique can induce a therapeutic effect on brain areas that otherwise remain difficult to target. rTMS may produce its analgesic effects, inducing motor cortex plasticity and activating descending inhibitory pain control systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 55 publications
(69 reference statements)
2
69
0
4
Order By: Relevance
“…Recently, indirect evidence has emerged that an additional mechanism, modulation of the descending pathways, can also play a role, as demonstrated for epidural motor cortex stimulation induced analgesia [40]. Onesti et al [41] showed that during TMS of M1 for pain relief in diabetic neuropathy the nociceptive R III reflex was reduced, and this is thought to represent an inhibitory action from descending neuromodulatory pathways. We found that M1 stimulation had a significantly greater analgesic effect than that of DLFPC, however the close association between prefrontal and motor areas is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, indirect evidence has emerged that an additional mechanism, modulation of the descending pathways, can also play a role, as demonstrated for epidural motor cortex stimulation induced analgesia [40]. Onesti et al [41] showed that during TMS of M1 for pain relief in diabetic neuropathy the nociceptive R III reflex was reduced, and this is thought to represent an inhibitory action from descending neuromodulatory pathways. We found that M1 stimulation had a significantly greater analgesic effect than that of DLFPC, however the close association between prefrontal and motor areas is well recognized.…”
Section: Discussionmentioning
confidence: 99%
“…[76][77][78] Moreover, using a H-coil designed to target the lower-limb motor cortex, analgesic effects have been obtained in patients with painful diabetic neuropathy. 79 …”
Section: Repetitive Tms (Rtms) and Theta Burst Stimulation (Tbs)mentioning
confidence: 99%
“…dTMS has opened a perspective to test new targets in a non-invasively way such as the insula and other areas involved in many aspects of pain sensation as emotion, behavior and pain control. A further interesting aspect is that rTMS apparently can foresee the effect of epidural MCS; consequently its use would improve the selection of patients to this invasive procedure [66]. Regarding invasive techniques, it is hard to believe that a randomized multicentric controlled doubleblinded study could be performed due to ethical and operational issues, but it seems to be an efficient approach based on prospective case-series reported.…”
Section: Future Prospectsmentioning
confidence: 99%